An overview of reductive trifluoromethylation reactions using electrophilic '+CF3' reagents. Issue 42 (21st October 2015) - Wang, Shi-Meng; Han, Jia-Bin; Zhang, Cheng-Pan; Qin, Hua-Li; Xiao, Ji-Chang
Graphical abstract: